Democracy and the Constitutional Monarchy in Malaysia: A Constitutional Analysis of Monarchical Discretion and Democratic Legitimacy, 1983–2022 - Osman, Samsul Kamil (Universitas Islam Negeri Raden Intan Lampung, 2025)
This article examines the evolving relationship between representative democracy and constitutional monarchy in Malaysia, focusing on the constitutional role and discretionary powers of the Malay Rulers and the Yang di-Pertuan Agong during political crises from 1983 to 2022. Rooted in historical compromise and shaped by postcolonial governance, Malaysia’s hybrid system features both electoral legitimacy and monarchical authority a balance that has repeatedly come under strain during moments of institutional uncertainty. The study adopts a qualitative, document-based methodology, analysing constitutional provisions, parliamentary records, royal statements, and judicial decisions. Drawing upon theories of popular and symbolic sovereignty, the research is guided by three core questions: (1) How does Malaysia’s monarchy operate within the framework of representative democracy? (2) How have discretionary powers been exercised in political transitions? (3) What reforms are necessary to harmonise monarchy and democratic legitimacy? Key case studies—including the 1983 and 1993 constitutional amendments, the 2009 Perak impasse, and the 2020–2022 Prime Ministerial appointments—highlight the monarchy’s expanded role during crises, revealing both stabilising functions and democratic tensions. A comparative analysis with other constitutional monarchies such as the United Kingdom, Japan, Thailand, Spain, and the Netherlands provides insight into best practices and institutional safeguards. The article concludes that while the monarchy remains a vital pillar of national unity, institutional reform is necessary to codify conventions, strengthen parliamentary supremacy, and modernise royal communication. Malaysia’s future political stability depends on a recalibrated relationship between monarchy and democracy one that is legally coherent, politically neutral, and aligned with civic expectations.